2013
DOI: 10.4161/cc.25099
|View full text |Cite
|
Sign up to set email alerts
|

Functional crosstalk between AKT/mTOR and Ras/MAPK pathways in hepatocarcinogenesis: Implications for the treatment of human liver cancer

Abstract: Hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related death worldwide, with limited treatment options. AKT/mTOR and Ras/MAPK pathways are frequently deregulated in human hepatocarcinogenesis. Recently, we generated an animal model characterized by the co-expression of activated forms of AKT and Ras in the mouse liver. We found that concomitant activation of AKT/mTOR and Ras/MAPK cascades leads to rapid liver tumor development in AKT/Ras mice, mainly through mTORC1 induction. To further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 39 publications
6
79
0
1
Order By: Relevance
“…In particular, ERK phosphorylates mitogen-activated protein kinase-interacting kinase (Mnk) 1 and 2, which are upstream of eIF4E [60]. Moreover, it is interesting that Mnk 1/2 activation has been detected both in vitro and in vivo in xenograft models, in response to tumor cell treatment with rapamycin, and that cotreatment with an Mnk 1/2 inhibitor potentiated the antineoplastic activity of rapamycin [61,62]. eIF4B significantly increases the helicase activity of eIF4A, which unwinds the secondary structure of the 5 0 untranslated region (UTR), allowing the 40S ribosomal subunit to bind to the mRNA [63].…”
Section: Reviewmentioning
confidence: 98%
“…In particular, ERK phosphorylates mitogen-activated protein kinase-interacting kinase (Mnk) 1 and 2, which are upstream of eIF4E [60]. Moreover, it is interesting that Mnk 1/2 activation has been detected both in vitro and in vivo in xenograft models, in response to tumor cell treatment with rapamycin, and that cotreatment with an Mnk 1/2 inhibitor potentiated the antineoplastic activity of rapamycin [61,62]. eIF4B significantly increases the helicase activity of eIF4A, which unwinds the secondary structure of the 5 0 untranslated region (UTR), allowing the 40S ribosomal subunit to bind to the mRNA [63].…”
Section: Reviewmentioning
confidence: 98%
“…Therefore, better survival outcomes may be achieved by using promising combinations of targeted therapies through inhibiting different pathways involved in HCC. Ras/MAPK and AKT/mTOR pathways are frequently deregulated in human hepatocarcinogenesis [141]. The combination of PKI-587, targeting PI3K/AKT/mTOR pathway and sorafenib, mainly targeting Ras/ Raf/MAPK signaling pathways, has the advantage over monodrug therapy on inhibition of HCC cell proliferation by blocking both the signaling pathways simultaneously [142].…”
Section: Combination Of Targeted Agentsmentioning
confidence: 99%
“…The study conducted by Krysan et al (15) indicated that PGE2 was able to induce the proliferation of colon and lung cancer cells through the activation of MAPK in an EGFR-independent manner in vitro. Wang et al (16) generated a mouse model characterized by the co-expression of activated forms of AKT and Ras in the liver. The results indicated that concomitant suppression of AKT/mTOR and Ras/MAPK pathways was highly detrimental for the growth of AKT/Ras-expressing cells in vitro.…”
Section: Introductionmentioning
confidence: 99%